IMPLEMENTASI WEBSITE INTERAKTIF UNTUK SISTEM MANAJEMEN PEMBAGIAN GAJI PERUSAHAAN - Osama Maulana Haq; Taftazani Ghazi Pratama; Widya Cholid Wahyudin (Universitas Muhammadiyah Kudus, 2025)
The implementation of a PHP Laravel-based payroll management system has proven to be an effective solution for optimizing company operations in terms of payroll and employee attendance management. With features including attendance data management, automated payroll calculation, deductions, and the ability to generate analytical reports, this system provides high transparency, efficiency, and accuracy. The use of Laravel as the primary framework ensures that the system is secure, flexible, and easily integrable with other modules. The outcomes of this implementation show improvements in strategic decision-making and employee satisfaction, ultimately supporting overall company performance and growth.Keywords: Transparency, Efficiency, and PHP Laravel